Leitura literária : uma proposta de trabalho envolvendo o direito da criança e do adolescente - Cintra, Elizabeth Dias de Souza (2015)
Reflecting on the didactic and methodological practices of literary reading experienced in classroom at elementary school is becoming ever more profitable and urgent. Thinking about it, this work proposes the analysis of literary representations in juvenile infants literary texts of children and adolescents rights as an atempt to develop activities of literary taste. This cut is relevant, because it enables the discussion of different social realities to the reader in training. To that purpose, it is intended that children and adolescents expand their horizon of expectations regarding their rights, yet challenging situations of abuse, exploitation of child labor, sexual abuse and other violations, and realize social tensions represented in literary texts. This concern is relevant because the school should be seen as a protection space for discussion and what is disrespect for the child and its consequences. For this, it is suggested in the methodological field a practice of reading the Gomes (2012) guided cultural model and the Bordini and Aguiar (1988) recepcional method. The search for a trampled teaching of literature in literary literacy is also a concern in this endeavor, and literary reading workshops were produced, on the pretense of developing more meaningful teaching strategies and attractive to our readers in training. To achieve these workshops, we have worked with literary texts: "Ciranda, cirandinha" by Arriete Vilela (2003) and "Por um pé de feijão," by Antonio Torres (2002). After the making and applicability of diverse activities, it culminated with the making of an educational notebook directed to the teacher, in order to spread our work proposal. As theoretical apparatus were used conceptions of literature teaching, reading and literary reading anchored in the postulates of Cosson (2011), Candido (2011), Dória (2008), Viegas (2012), Werneck (2010), Eco (2004), Leffa (1996), Magnani (2001), Silva (2009), Lajolo and Zilberman (2007) among others; in addition the study on violence against children and adolescents supported in Vicente Faleiros and Eva Faleiros (2007), Philippe Ariès (2014), Moura (2013), Passetti (2013) and as the concepts and guidelines regarding juvenile infants public rights established by the Statute of Children and Adolescents (1990).